High Resolution of Water Availability for Emilia-Romagna Region over 1961–2015. (14th November 2018) - Cervi, F.; Nistor, M. M.
Abstract : In this study, monthly time series of precipitations and temperatures from 1024 controlled and homogeneous meteorological stations located in the Emilia-Romagna region (northern Italy) are processed in order to assess potential climate changes that occurred during the period 1961–2015. Normal period as baseline between 1961 and 1990 (1990s) and recent period between 1991 and 2015 (2010s) were adopted in this study to analyse the possible effect of climate change on water availability during long-term period. Based on monthly and annual temperature (TT), precipitation (PP), and potential (ET0), the actual evapotranspiration (AET0) and water availability (WA) were computed at high spatial resolution. Between the two analysed periods, during the 2010s, it was found an increase in the maximum mean annual temperature by 1.08°C while the maximum mean annual precipitation saw a slight decrease (from 2222 mm to 2086 mm). The precipitation decrease is more intense in the South and West sectors of area (8%) and mainly depends on negative changes taking place during the winter and the beginning of spring (from December to March). The maximum mean annual ET0 and AET0 reached values of 663 mm and 565 mm during the 1990s, while during the 2010s, the found values were 668 mm and 572 mm, respectively. Because of the decrease in precipitation and increase in the ET0 and AET0, the WA (the proportion of precipitation that is available at the soil surface for subsequent infiltration and runoff processes) shows a reduction (about 10–20%) in the whole region, with exception of the North-East part of the Emilia-Romagna region. The decrease in the mean annual water availability induces severe issues concerning the water resources management across the whole Emilia-Romagna region.